(3ebOeI aj GdEbJUGO GdbjGSj (B/s - (3GdbQjTj, eMeO UGdM JQcjs ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B, s, 2004)
(3JYQja Yde GdEbJUGO GdbjGSj(B- (3fXQjI GdEQJHGW(B- (3WHjYI JMdjd GdEfMOGQ(B- (3JMdjd GdEfMOGQ GdHSjW(B- (3fehPL GdEfMOGQ GdNWj GdHSjW hWQjbI GdeQHYGJ GdUZQi GdEYJjGOjI(B- (3GdEfMOGQ GdeJYOO(B- (3JMdjd GdJHGjf(B- (3eTcdI GdEQJHGW GdNWj GdeJYOO(B- (3eTcdGJ GdEfMOGQ(B- (3CSdhH GdeUahaGJ aj JMdjd GdEfMOGQ(B- (3feGPL GdeYOdGJ GdBfjI(B- (3GdJTNjU GdEMUGFj(B- (3JWHjbGJ hJeGQjf eMdhdI(B.s
(3GdeQGLY U(B. 363s
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdQjGVjs; (3GdEbJUGO GdbjGSjs